Psychological features of the situational model of economic behavior - Voskanyan, Karlen (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
The problem of modeling economic behavior, traditionally related to the field of economic science, today has also become the subject of study of philosophy, sociology, psychology and jurisprudence. The interdisciplinary interest in the problem is not accidental, since issues related to the causes and patterns of economic behavior have acquired an important social significance. The economic behavior of members of society as consumers today has become unpredictable and does not obey the algorithms of economic calculation. It is necessary to identify models of economic behavior that are beyond the scope of economic theory studies and require research in related fields. In this regard, such studies related to the problem of economic behavior, which also take into account the individual and ethno-psychological characteristics of a person, have become relevant in psychological science.The article presents the essence of the problem of modeling economic behavior, some economic, psychological and sociological approaches to the problem. A situational model of economic behavior is considered, in which individual psychological characteristics of a person and socio-psychological factors act as variables. The characteristic features of the model are listed, which are determined by the ability of self-regulation of the individual, the value system of the individual and the motivation to achieve success.
Keywords: economic behavior; modeling; rationality of behavior; psychological factors; self-regulation; value system; motivation; situational model